The Correlation between Residential Density and Greenhouse Gas Emissions in Surabaya City - Setiawan, Rulli Pratiwi; Umilia, Ema; Handayeni, Ketut Dewi Martha Erli (International Journal of Planning and Development, 2014)
Abstract: Population growth is happening in cities, including Surabaya as the second largest metropolitan region in Indonesia. The population growth has an impact to the residential density, whereas residential is usually the largest part of land use in urban areas. In Surabaya, residential use covers more than 60% of the total area. The intensive use of residential area has impacts on the environment. One significant issue is the consumption of energy that produces greenhouse gas emissions. This study is aimed at explaining the relationships between residential density and greenhouse gas emissions in Surabaya City, Indonesia. The residential density will be divided into three categories, i.e. low, medium and high density. The category of density is taken from the Identification Report of Surabaya Spatial Plan. The results of this study indicate that there are significant differences in the electrical energy consumption for the household sector in each residential density. These differences are mainly influenced by variables such as car ownership, ventilation system, the use of electrical power, cooking fuel and the way to use the home appliances. The highest total energy consumption per month exists in high density type. Although the average smallest energy consumption per household exists in medium density, the total energy consumption in medium density is much greater than that in the low density because the number of households in medium density is greater. The final result shows that the correlation between the total production of GHG emissions (CO2) and density has a direct or positive relationship, which means that the greater the density, the higher the production rate of GHG emissions (CO2).Keywords: correlation, greenhouse gas emissions, land use, residential density, settlements, urbanÂ